CHOOSING A COMPRESSION STANDARD FOR TRANSMITTING A TELEVISION IMAGE - Amreev, M.; Safin, R.; Yakubov, V.; Pavlova, T. (Academic Scientific Journal of Computer Science, 2020)
With the advent of the MPEG-4 Visual and H.264 compression standards, the role of the MPEG-2 compression standard has not diminished at the present time, since these standards are largely compatible, especially for information highways. Today, in a number of countries, the MPEG-2 compression standard is actually the main one for broadcasting, the functioning of which is based on the operation of DVB-T terrestrial digital television systems. Due to the fact that the majority of the currently used STBs support the MPEG-2 standard, it will remain widespread for at least the next few years. The ITU-T H.264 /MPEG-4 Part 10 AVC standard (abbreviated as H.264/AVC) is a promising new technology for encoding and compressing audiovisual information. The compression efficiency of the H.264/AVC standard is higher than the MPEG-2 standard with equal visual perception. The H.264/AVC standard was developed independent of the transport layer of the transmission systems used. Therefore, information delivery in the H.264/AVC standard can be carried out using any existing transmission and broadcasting systems, including: systems with IP protocols (including streaming delivery), transport streams of broadcasting systems in the MPEG-2 standard, as well as specific formats H.264 / AVC files for storage and processing on servers.